PENERAPAN METODE KANSEI ENGINEERING DAN QUALITY FUNCTION DEPLOYMENT (QFD) DALAM PENGEMBANGAN KUALITAS PRODUK PIAMA - Wirahata, Christie; Kosasih, Wilson; Salomon, Lithrone Laricha (Jurnal Ilmiah Teknik Industri, 2023)
This research was conducted in a micro, small and medium enterprise (MSME) which produces apparel with its own brand. Even though they have been producing clothes since October 2020, sales have not met the target so the owner decided to temporarily stop the business with plans to continue after having sufficient capital. This study aims to determine consumer expectations for pajama products, measure the gap between expectations and products, and provide a design for the development of product quality using the Kansei Engineering and Quality Function Deployment (QFD). By processing the results of the first questionnaire and grouping the attributes into the eight dimensions of product quality, the eight most important attributes were comfort, pockets on shirt, safe, durable, smooth, easy to buy, affordable, and minimalist. The second questionnaire asked respondents to express their level of expectations and perceptions of the main product, competitor 1 and 2, which were then used to conduct a gap analysis. The gap value showed that consumer satisfaction with the main pajama product is lower than competitor 1, but higher than competitor 2, where the main product has an advantage in the 'affordable price' attribute. Furthermore, the three phases of the House of Quality (HOQ) provided manufacturing planning results in the form of using materials without defects, cotton and cotton t-shirt materials, plain or minimalist motifs, short sleeve and short pants model, variations in sizes M, L, and XL for all models, and the provision of pockets in shirts and pajama pants.